2020
DOI: 10.1016/j.nicl.2020.102380
|View full text |Cite
|
Sign up to set email alerts
|

Newborn amygdalar volumes are associated with maternal prenatal psychological distress in a sex-dependent way

Abstract: Highlights Assessed relation of maternal prenatal distress to amygdalae and hippocampi volumes. Newborn amygdalar volumes negatively related to maternal prenatal distress in males. No association between maternal prenatal distress and newborn hippocampal volumes. Prenatal maternal distress seems to affect newborn brain in a sex-dependent way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 115 publications
3
34
0
Order By: Relevance
“…It is challenging to place the magnitude of this observed effect in the context of previous findings in the literature, given the small number of studies of this or similar research questions, differences in statistical approach, and/or absence of reported effect size estimates. However, it is apparent that the size of the effect of maternal perceived stress on newborn HCV in our study is consistent with that reported in studies of maternal psychosocial stress and other subcortical structures ( Lehtola et al, 2020 ), and also with a study reporting a prospective association between serial measurements of perceived stress across a 20-year period and HCV in postmenopausal women ( Gianaros et al, 2007 ). Moreover, the effect in our study of maternal stress on infant social-emotional development via offspring HCV may portend clinical relevance.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It is challenging to place the magnitude of this observed effect in the context of previous findings in the literature, given the small number of studies of this or similar research questions, differences in statistical approach, and/or absence of reported effect size estimates. However, it is apparent that the size of the effect of maternal perceived stress on newborn HCV in our study is consistent with that reported in studies of maternal psychosocial stress and other subcortical structures ( Lehtola et al, 2020 ), and also with a study reporting a prospective association between serial measurements of perceived stress across a 20-year period and HCV in postmenopausal women ( Gianaros et al, 2007 ). Moreover, the effect in our study of maternal stress on infant social-emotional development via offspring HCV may portend clinical relevance.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, one recent study using fetal MRI reported an association between maternal psychosocial distress and fetal left HCV ( Wu et al, 2020 ). In contrast, two other studies ( Lehtola et al, 2020 ; Qiu et al, 2013 ) found no associations between maternal depressive and anxiety symptoms during pregnancy and newborn HCV (although maternal antenatal anxiety was associated with slower growth of the right hippocampus across the first 6 months of life ( Qiu et al, 2013 )).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations